37. EVALUATION OF THE RESULTS OF PHACO SURGERY TO TREAT CATARACTS IN EYES WITH PSEUDOCAPSULAR DETACHMENT SYNDROME AT HOSPITAL 19-8 (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluate the results of Phaco surgery on eyes with pseudocapsular detachment syndrome; study complications and treatment during and after surgery.Subjects and methods: Clinical intervention study, 30 eyes of 30 patients with cataract in eyes with pseudocapsular detachment syndrome underwent Phaco surgery to place monofocal artificial lenses, followed up 1 week, 1 month, 3 months after surgery.Results: 93.4% of eyes had visual acuity > 5/10. Average visual acuity was 0.63. Intraocular pressure was reduced by 2.0 mmHg. Complications of anterior capsule tear 3.3%, posterior capsule tear, vitreous escape 6.7%, Descemet membrane detachment 3.3%. Complications of keratitis 16.7%, uveitis 6.7%, anterior capsule fibrosis 3.3%, posterior capsule opacification 6.7%. Intervention of small poorly dilated pupils by pupil dilation technique or using iris hooks gave good results.Conclusion: Phaco surgery on pseudocapsular detachment eyes is a difficult technique, requiring highly skilled surgeons. To ensure safe and effective surgery on pseudocapsular detachment eyes, surgeons need to carefully plan the surgery to limit complications.
Keywords: Cataract; pseudocapsular detachment; Phaco surgery.